IMPLEMENTATION OF THE INDEPENDENT CURRICULUM POLICY TO IMPROVE IN-DEPTH LEARNING AT SMPN 12 SINGKAWANG - Rahmadanti; Raden Imam Al Hafis (Yayasan Wayan Marwan Pulungan, 2026)
This research examines the implementation of the Independent Curriculum policy in enhancing in-depth learning at SMPN 12 Singkawang. A qualitative descriptive approach was employed, with data collected through observations, in-depth interviews, and documentation. The findings indicate that the implementation has achieved a high level of effectiveness. Teacher readiness and institutional support are relatively strong, yet challenges such as administrative workload and limited school facilities persist. Internal facilitators are ineffective due to time constraints. The study concludes that while the implementation of the Independent Curriculum is positive, it requires a simplified administrative structure and technical support from an internal facilitator team to realize in-depth learning across all subjects.